Smart Relay-Based Control System for Reverse Osmosis Drinking Water Treatment: Sistem Pengendalian Berbasis Relay Cerdas untuk Pengolahan Air Minum dengan Teknologi Osmosis Terbalik - Armadani, Mochammad; Syahrorini, Syamsudduha (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Access to safe drinking water remains a critical challenge in Indonesia, with nearly 30% of the population lacking proper access. Specific Background: Reverse Osmosis (RO) technology provides a solution for producing clean water, but conventional systems still face issues of efficiency, reliability, and safety. Knowledge Gap: Limited studies document the integration of automated control systems with RO units in real-world industrial applications. Aim: This study aims to develop and test a drinking water treatment control system using Schneider Smart Relay integrated with pH and TDS sensors. Results: Experiments on four water samples showed average pH of 7.67 (input), 7.80 (reject), and 7.86 (output), while average TDS values were 136 ppm (input), 298 ppm (reject), and 33.5 ppm (output). The system automatically activated or deactivated pumps according to preset water quality parameters, with buzzer alerts for anomalies, ensuring compliance with health standards. Novelty: The system combines automation, energy efficiency, and safety through smart relay integration, offering advantages over conventional RO setups. Implications: Findings demonstrate that this system can improve water treatment reliability and is suitable for household and industrial-scale implementation. Highlight: Automated RO system improved efficiency and water quality control Smart relay integration ensured safety and energy savings Applicable for household and industrial water treatment needs Keywords: Reverse Osmosis, Smart Relay, Drinking Water, pH Sensor, TDS Sensor